A novel splicing variant of small nucleolar RNA host gene 4 is a podocyte-selective non-coding RNA upregulated in response to puromycin aminonucleoside-induced podocyte injury. (31st December 2018) - Horikawa, Aya; Yoneda, Tomomi; Yaoita, Eishin; Yamaguchi, Katsushi; Shigenobu, Shuji; Kuramochi, Mizuki; Yamate, Jyoji; Inui, Takashi; Ishibashi, Osamu
Abstract: Podocytes are terminally differentiated cells that function as the glomerular filtration barrier in the kidney, and podocyte injury leads to serious proteinuria and podocyte leakage into urine. Recent studies have demonstrated that the number of urinary podocytes is correlated with the progression of glomerular diseases. Therefore, urinary podocytes may serve as an indicator of podocyte injury. In this study, to explore podocyte injury-related genes, we performed comprehensive transcriptome analysis of primary rat podocytes cultured in the presence or absence of puromycin aminonucleoside (PAN), an agent commonly used to induce podocyte injury. RNA-seq revealed that a transcript containing the intronic sequence of small nucleolar RNA host gene 4 ( Snhg4 ) was expressed in podocytes and upregulated by PAN. RT-qPCR analysis demonstrated that this transcript, but not Snhg4, was selectively expressed in podocytes. Therefore, we designated the novel transcript Snhg4-pod. 5′- and 3′-RACE experiments revealed that Snhg4-pod is a novel splice variant of Snhg4 lacking a poly(A) tail. PAN induced Snhg4-pod expression in podocytes in a dose-dependent manner along with their mitochondria-mediated apoptotic cell death. Further, Snhg4-pod was detected in urinary sediments from PAN-induced nephrotic rats. Our findings suggest that Snhg4-pod may serve as a novel marker for the diagnosis of glomerular injury.